New Challenges in Economic and Business Development – 2021: Post-Crisis Economy: PROCEEDINGS; (13th International Scientific Conference, May 14, 2021, Riga, University of Latvia) - (:unkn) unknown (University of Latvia, 2021)
This year's conference was devoted to the challenges related to the post-crisis economic development. Crisis is often seen as an opportunity, stimulating change of traditional approaches and often leading to creation of new systems. The objective of the conference is to provide a platform/opportunity for scholars, researchers and professionals from different disciplinary backgrounds to meet, exchange ideas, findings, research results and discuss challenges and prospects for economic and business development.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics; marketing; management; business; development; pension system; public sector; market; COVID-19 pandemic; innovations; corporate social responsibility; economic policy; digitalization; migration; demography; company growth